MBE growth and characterization of gold-catalyzed gaas-algaas core-shell nanowires on silicon (111) substrates - Ibañes, Jasher John A.; Somintac, Armando (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
GaAs-AlGaAs core-shell nanowires were grown on Si (111) substrates using Au-catalyst assisted solid source molecular beam epitaxy (MBE). The core-shell nanowires were characterized by scanning electron microscopy (SEM) and photoluminescence spectroscopy. SEM of the grown nanowires shows that they are of high density; oriented in the <111> direction; and that they were grown by the vapour-liquid-solid mechanism. Room temperature photoluminescence shows that core-shell nanowires have strongly enhanced optical quality compared to bare GaAs nanowires.
Thesis (M.S.Physics)--University of the Philippines Diliman
Keywords: Molecular beam epitaxy; Silicon